Investigation of the Coumarin Content of Cassia nodosa Leaves Growing in Egypt - Hussein Ahmed, Amal (Asian Journal of Chemistry, 2011)
Four natural coumarins were isolated from the leaves of Cassia nodosa. The structures of these coumarins were established by spectroscopic data mainly 1H NMR, 13C NMR and EIMS. Hydro alcoholic extract of Cassia nodosa showed a potent effect in lowering blood sugar levels in normal and streptozotocin induced diabetic model rats, when compared to controls.